Application of crystal field theory to the infrared spectra of transition metal complexes - Shephard, Gordon Seymour (Department of Chemistry, 2024)
[pages missing] problem in the IR spectra of 8-quinolinol chelqtes of di~ and trivalent metals of the first transition series. The metal-sensitivity of bands in the IR spectra of structura~ly differing substituted 8-quinolinol Qhelates ~eceives an interpretation in terms of crystal field theory. The effect of halogen and methyl substituents in the I~ spectra of the Cu(II) chelates is consistent with the band assignments based on crystal field effects P.nd is relat;.ep to both the resonance and inductive capacities of th~ substituents. A total of 232 compounds have been synthesized and are discussed.